2018
DOI: 10.7759/cureus.2921
|View full text |Cite
|
Sign up to set email alerts
|

Spilled Gallstones Silent for a Decade: A Case Report and Review of Literature

Abstract: Laparoscopic cholecystectomy is associated with complications such as gallbladder perforation and spillage of gallstones. While these shortcomings are common, the occurrence of the resultant nuisances, such as intra-abdominal abscesses, is infrequent. We present the case of an individual who developed an intra-abdominal abscess following a spillage of gallstones, which occurred after a laparoscopic cholecystectomy that was performed more than a decade ago. Herein, we also discuss the findings of a literature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In high-risk situations, it is essential for surgeons to be vigilant for gallbladder perforation and gallstone spillage. If there are spilled gallstones, it is recommended to do preventative measures for infection by irrigation with saline to dilute bile contents and retrieve all stones [ 9 ]. Previous studies do not support switching to open surgery as it increases patient morbidity [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In high-risk situations, it is essential for surgeons to be vigilant for gallbladder perforation and gallstone spillage. If there are spilled gallstones, it is recommended to do preventative measures for infection by irrigation with saline to dilute bile contents and retrieve all stones [ 9 ]. Previous studies do not support switching to open surgery as it increases patient morbidity [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study conducted by Yethadka et al in 2014, 76.8% of the participants thought that two years were sufficient to follow up after spilled stones and that they had no knowledge about the possibility of delayed complications [4]. In the literature, complications from unretrieved gallstones have been described as occurring years or even decades later [15][16][17]. Morris et al reported a 71 year-old-female who presented with complete bowel obstruction 15 years after LC [18].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, bedside ultrasound not only allowed for rapid diagnosis of the pseudoaneurysm, but also allowed for identification of the associated perihepatic abscess, diaphragmatic disruption, and communicating right pleural effusion with empyema. These are also rare complications of laparoscopic cholecystectomy that have often been associated with spilled and retained gallstones 4 …”
Section: Diagnosismentioning
confidence: 99%